REVAT (Recurrent Varices After Treatment) - Noppeney, T.; Nüllen, H. (Phlebologie, 2009)
The term “recurrent varicose veins” covers various entities. In the first instance, recurrent varicose veins may be the progression of the underlying disease, as there is a hereditary disposition to the condition, but we also find the phenomenon of neovascularisation, and lastly we repeatedly see recurrent varices as a result of technical or strategic surgical errors and the failure of endovenous procedures. No differentiation between these different types of recurrent varicose veins has previously been made in the literature, so that the numbers given vary between 6% and 60%. Up to the present time, few data on the progression of the underlying disease are to be found in the literature. Our own studies, on average 36 months postoperatively, demonstrated new varicose side branches that could be interpreted as progression of the underlying disease in 56.8% of the patients followed up.Several recent publications demonstrate neovascularisation as a cause of recurrence. While some authors give a figure of 24% for recurrence due to neovascularisation in patients who have had surgery, other publications regard neovascularisation as the main cause of postoperative recurrence.The data on technical or strategic surgical errors and recanalisation after endovenous procedures are also very varied. Numbers for technical errors as the cause of recurrent varicose veins following surgery range from 10.7% to more than 70%. Published recanalisation rates after endovenous laser therapy vary between 0% and 36%; the average recanalisation rate in the available prospective randomised studies on radiofrequency obliteration was 12.9%. Foam sclerotherapy has recanalisation rates between 69% and 86%, with a mean follow-up of 32.2 months.Given the different possible causes, it is extremely important, that recurrent varicose veins should be classified. The authors have developed a simple classification that can be used in routine daily practice. Recurrent varicose veins are given the acronym REVAT (recurrent varices after treatment). Generally speaking, on the one hand there is progression of the underlying disease (progression of disease = PD) and, on the other hand, varicosities after treatment as a result of technical error or failure of the method used (recurrence after treatment = RT). Progression of the underlying disease can be further subdivided into neovascularisation at the saphenofemoral or popliteal junction (progression of disease at the junction = PD-J) and new varices arising in the treated vascular territory (progression of disease at the limb = PD-L).In the case of recurrent varices after treatment we distinguish between a persisting or a new reflux at the saphenofemoral or the popliteal junction (recurrence after treatment at the junction = RT-J), untreated segments of the great or small saphenous veins or recanalisation of the trunk (recurrence after treatment at the trunk = RT-T) and untreated side branches or perforating veins (recurrence after treatment at side branches = RT-S). With the help of these abbreviations a simple formula can be generated to describe the recurrent varices, e.g. recanalisation of the left great saphenous vein (GSV) after endovenous treatment and a new varicosis in the vascular territory of the left great saphenous vein resulting from progression of the underlying disease: vascular territory left great saphenous vein = GSV-L, technical or tactical error due to recanalisation of the GSV = RT-T, progression of the underlying disease in the vascular territory of the GSV = PD-L. This generates the formula: GSV-L : RT-T, PD-L.Since there are no exact figures on the incidence of the individual causes of recurrent varicosis, a classification of recurrent varicosis is indispensable to ensure clarity in the future.
Keywords: Recurrent varicose veins; classification; REVAT